To disclose or not to disclose: A systematic review of factors associated with disclosure and concealment of mental illnesses - Gnainsky, Miri; Roe, David; Negri-Schwartz, Ofir; Cohen-Chazani, Yael; Lavidor, Michal; Hasson-Ohayon, Ilanit (Clinical psychology review, 2025)
The decision to disclose or conceal a mental illness represents a complex dilemma influenced by various personal, social, and environmental factors. Through a systematic review of 42 quantitative studies published until May 2025, we examined how individuals manage mental illness disclosure and secrecy, and their associations with mental health outcomes, perception-related variables, and functional outcomes. Findings show that secrecy had consistent negative associations with mental health outcomes including depression, well-being, and quality of life, while disclosure's associations with outcomes varied across different contexts. Second, self-perception-related variables, particularly stigma, played a central role – with studies showing different patterns of associations between disclosure and both self-stigma and public stigma. Third, selective disclosure emerged as a strategy for managing disclosure processes across different social contexts. In employment settings, mixed findings emerged regarding disclosure outcomes, with some studies showing associations with job matching and duration, although these varied by workplace context. Several factors that influenced the observed associations were identified, including perceived social support and contextual factors. Notably, disclosure and secrecy operated as distinct rather than opposite processes, with individuals often managing both simultaneously across different contexts. These findings highlight the need for nuanced approaches to supporting disclosure decisions, considering both personal and environmental factors in clinical practice and organizational interventions. •Secrecy and disclosure of mental illness operate as distinct processes rather than opposite ones.•While secrecy shows negative psychological outcomes, disclosure effects are dependent on context.•Social support and contextual factors related to mental illness disclosure decisions.•Selective disclosure appears as a common approach in managing mental health information.•Review suggests the need for individualized approaches to supporting disclosure decisions.